Analisis pengaruh kemelekan keuangan syariah dan Risk Appetite terhadap minat mahasiswa untuk berinvestasi: Studi pada mahasiswa Kota Malang - Putri, Laurina Trisnaning (Maliki Interdisciplinary Journal, 2023)
The major goal of this study is to determine how risk tolerance and sharia financial literacy affect students' investing interests in Malang City. The population of this study was made up entirely of pupils from Malang City, and the author used a quantitative descriptive methodology. It can be shown that the existence of sharia financial literacy and risk appetite affect the interest of Malang City students since the data collection method is a questionnaire and the data analysis is basic linear regression analysis. This is demonstrated by the 0.442 correlation coefficient between Islamic financial literacy and risk tolerance and investment interest, which indicates a high and positive association.